Comparing approaches for numerical modelling of tsunami generation by deformable submarine slides - Smith,R; Hill,J; Collins,GS; Piggott,MD; Kramer,S; Parkinson,S; Wilson,C (Ocean Modelling, 2016)
Tsunami generated by submarine slides are arguably an under-consideredrisk in comparison to earthquake-generated tsunami. Numerical simulationsof submarine slide-generated waves can be used to identify the important factorsin determining wave characteristics. Here we use Fluidity, an open sourcefinite element code, to simulate waves generated by deformable submarineslides. Fluidity uses flexible unstructured meshes combined with adaptivitywhich alters the mesh topology and resolution based on the simulationstate, focussing or reducing resolution, when and where it is required. Fluidityalso allows a number of different numerical approaches to be taken tosimulate submarine slide deformation, free-surface representation, and wavegeneration within the same numerical framework. In this work we use amulti-material approach, considering either two materials (slide and waterwith a free surface) or three materials (slide, water and air), as well as asediment model (sediment, water and free surface) approach. In all casesthe slide is treated as a viscous fluid. Our results are shown to be consistentwith laboratory experiments using a deformable submarine slide, anddemonstrate good agreement when compared with other numerical models.The three different approaches for simulating submarine slide dynamics andtsunami wave generation produce similar waveforms and slide deformationgeometries. However, each has its own merits depending on the application.Mesh adaptivity is shown to be able to reduce the computational cost withoutcompromising the accuracy of results.